NEW VARIETY OF LOW-TEMPERATURE METASOMATIC ROCK - Shcherban I.P.; Kopylova L.V.; Shevchenko V.I. (My University, 1990)
This paper attempts to fill the gap for some metasomatites from western Uzbekistan, where they accompany rare-metal mineralization. The ore field in which we worked consists of Carboniferous sedimentary and volcanosedimentary rocks. Variously altered and collected in an anticlinal fold. Granite and granodiorite, as well as a complex of kersantite, spessartite and diorite-porphyry dikes, are the chief igneous rocks present in the field. All three columns described are products of the same metasomatic process. The differences between them are not fundamental, but consist mainly of different ratios of the main rock-formating minerals, governed by the composition of the parent rocks. On the one hand these rocks are similar to beresite, and on the other, to albite-carbonate metasomatites (eisite). As in typical beresite, chlorite is fairly extensively developed in the outer zone, sericite and magnesian-iron carbonate dominate in the middle zone, and quartz and carbonate in the inner. But in contrast to beresite, these rocks are relatively high in albite in the inner and sometimes in the middle zones. It is in this feature, repeatedly confirmed by the X-ray structural and chemical analyses, that the rocks in question resemble eisite.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная